42nd AIAA Plasmadynamics and Lasers Conference 2011
DOI: 10.2514/6.2011-3282
|View full text |Cite
|
Sign up to set email alerts
|

Recent AAOL In-Flight Wavefront Measurements of Aero-Optics and Implications for Aero-Optics Beam Control in Tactical Laser Weapon Systems

Abstract: Aero-optics disturbances were measured in-flight with the Airborne Aero-Optics Laboratory (AAOL) 1 ft (4 in. clear aperture) flat-windowed turret at an altitude of 15 kft altitude and at a Mach number of 0.5 for 47 az., 42 el. (forward-looking) and 139 az., 70 el. (rearlooking) turret angles. Wavefronts were collected using a FasCam CCD array camera with an AMO lenslet array in a Shack-Hartman configuration at a 20 kHz frame-rate. 2,000 consecutive wavefronts of each of the two turret pointing angles measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…However, recent computational fluid dynamics (CFD) simulations and measurements from wind tunnel and flight experiments have shown that aero-optical aberrations have sufficiently high spatial and temporal bandwidth to sometimes exceed the limits of conventional AO control systems. For greater look-back angles, where separated shear layers exhibit coherent vortical structures with correspondingly large density (and hence index of refraction) variations, 6 conventional AO may be insufficient, 7 and a more advanced AO control technique 8,9 and/or flow control 10 may be required. Furthermore, the air flow around and over turrets with flat and conformal windows is complicated, consisting of several interacting flow phenomena such as horn vortices, necklace vortices, flow separation, shear layer formation, Kelvin-Helmholtz vortices, separation bubbles, recirculation regions, turbulent wakes, and von Kármán vortex shedding.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent computational fluid dynamics (CFD) simulations and measurements from wind tunnel and flight experiments have shown that aero-optical aberrations have sufficiently high spatial and temporal bandwidth to sometimes exceed the limits of conventional AO control systems. For greater look-back angles, where separated shear layers exhibit coherent vortical structures with correspondingly large density (and hence index of refraction) variations, 6 conventional AO may be insufficient, 7 and a more advanced AO control technique 8,9 and/or flow control 10 may be required. Furthermore, the air flow around and over turrets with flat and conformal windows is complicated, consisting of several interacting flow phenomena such as horn vortices, necklace vortices, flow separation, shear layer formation, Kelvin-Helmholtz vortices, separation bubbles, recirculation regions, turbulent wakes, and von Kármán vortex shedding.…”
Section: Introductionmentioning
confidence: 99%
“…POD modes can be used to form reduced-order models of the flow by projecting the governing equations onto them 16 . They are also potentially useful in adaptive optics applications, since they provide lenslet array shapes that would counteract the largest aero-optical effects 19 . In the present case, the POD modes of the wavefront in the beam serve two purposes.…”
Section: B Proper Orthogonal Decomposition Analysis Of Opdmentioning
confidence: 99%
“…气动光学贯穿从激光的产生、 传输以及到达目标的全过程。例如, 气体激光器内流场、 气动窗口气动光 学 , 机 载 平 台 光 学 接 收/发 射 窗 口 附 近 边 界 层/剪 切 层 、 尾 流 与 光 束 的 相 互 作 用 , 剪 切 风 对 大 口 径 地 基 天 文 系 统成像的影响等 [1][2][3][4][5] 。只是在机载/弹载光学系统广泛应用的今天, 探讨飞行器高速飞行时光束穿过接收/发 射窗口附近流场发生畸变的机理、 精确测量光束通过流场后的变化量及研究其自适应校正方法才显得尤为 重要。 例 如 , 当 导 弹 在 大 气 层 内 高 速 飞 行 时 , 其 光 学 头 罩 与 大 气 之 间 产 生 剧 烈 的 相 互 作 用 , 由 于 气 动 力 、 气 动 热 等 原 因 使 头 罩 周 围 的 气 体 密 度 发 生 剧 烈 变 化 , 导 致 在 光 束 的 传 输 通 道 上 产 生 严 重 的 折 射 率 非 均 匀 分 布 。 目标发出的光束经大气传输后依次穿过激波、 边界层/剪切层以及探测窗口制冷剂流动层, 最后聚焦在光学 寻 的 器 光 敏 阵 列 焦 平 面 上 , 形 成 目 标 图 像 。 边 界 层 、 冷 却 剂 流 动 层 与 周 围 高 速 流 场 形 成 的 非 均 匀 剪 切 层 使 得 寻 的 器 光 学 成 像 系 统 中 目 标 像 的 像 差 急 剧 增 加 , 从 而 降 低 目 标 图 像 的 清 晰 度 和 位 置 探 测 的 准 确 度 。 因 域防御系统(THAAD)" 的拦截弹, 我国的新型高精度 HQ 导弹等都不可避免地遇到了气动光学问题 [6] 。 在机载激光的传输过程中, 光束不可避免地通过发射窗口附近的边界层/剪切层、 尾流等复杂流动, 导致 光束在远场的能量减弱, 甚至消失。对于短波长( λ ≤ 2 μm )系统, 飞行器表面的边界层/剪切层均会带来严 重的气动光学效应 [7][8] , 例如, 美国空军的 KC-135 机载激光飞行实验表明, 边界层导致 He-Ne 激光在远场的 斯特雷尔比 Rs 降低至 0.27 [1] ; 2010 年, 美国导弹防御局的机载激光(ABL)武器密集地进行了多次打靶试验, 但 按 照 战 场 要 求 , ABL 仍 有 许 多 关 键 问 题 需 要 解 决 , 美 军 " 机 载 激 光 武 器 " 项 目 现 已 改 为 " 机 载 激 光 试 验 台 " (ALTB)项 目 。 2013 年 美 国 国 防 高 级 研 究 计 划 局 应 用 研 究 领 域 的 先 进 战 术 技 术 专 题 依 然 将 " 提 高 战 术 飞 机 上 高 能 激 光 器 的 性 能 , 以 更 好 地 对 付 机 尾 方 向 的 目 标 [9] " 列 入 资 助 范 围 , 这 里 特 别 提 到 " 机 尾 方 向 的 目 标" 就 是因为上游的边界层发生分离后形成流动状况更为复杂的剪切层或尾流, 对光束传输的影响也更大; 此外, 2011~2013 年 期 间 , 美 国 空 军 的 有 关 气 动 光 学 问 题 的 理 论 及 实 验 研 究 文 献 更 是 高 密 度 地 见 诸 报 道 [10][11][12][13][14][15]…”
Section: 引 言unclassified